Implementation of Guided Imagery Therapy in Reducing Blood Pressure Among Family Members of Elderly Individuals with Hypertension - Ananda, Putri Awaliah; Nurhayati, Nurhayati; Sanghati, Sanghati; Mala, Yanti (LPPM STIKes Muhammadiyah Ciamis, 2025)
Introduction: Hypertension or high blood pressure is an abnormal increase in blood pressure in the arteries that carry blood from the heart and pump it to all tissues and organs of the body continuously for more than a period. Hypertension is blood pressure of more than or equal to 140 mmHg in systole and more or equal to 90 mmHg in diastole. Research objectives: This case study aims to determine the effect of implementing guided imagery therapy in reducing blood pressure in family members of elderly hypertension sufferers. Method: in this study the method used was interviews and observation subjectively and objectively. Results: The results of this case study show that after GUIDED IMAGERY therapy was carried out there was an effect in lowering blood pressure. Conclusion: it can be concluded that in conducting a case study of GUIDED IMAGERY therapy. can reduce blood pressure in hypertensive patients. Suggestion: Recommended for writers, it can be a reference for gaining knowledge and deepening and broadening insight in preparing scientific paper proposals.